Pengaruh Fasilitas Terhadap Kepuasan Tamu di Legen Villa Lubuk Minturun - Fadlis, Khildayani; Retnaningtyas Susanti (CV. ITTC INDONESIA, 2024)
This research was motivated by the discovery of problems related to facilities to guest satisfaction. The research aims to obtain information and describe the influence of facilities on knowledge satisfaction at Legen Villa Lubuk Minturun. The method used in this study is quantitative. Using primary data and secondary data. Guests who have stayed and who are staying are the population of this study. The sample used in this study amounted to 85 guests with a non-probability sampling technique. Data collection was carried out by using a questionnaire based on a likert scale that has been tested for validity and reliability. The tool used for data processing is SPSS 25. The results obtained from the study were that the facility variable was classified as sufficient based on statistical calculations with an average respondent achievement rate (TCR) of 72% and guest satisfaction was classified as a good category based on statistical calculations with an average respondent achievement rate (TCR) of 79.35%. In this study, the Beta or Satandardized Coefficient value of the facility variable (X) was 0.408 with a Thical value (3.225) with a significance of 0.002 < 0.05, which showed that the facility variable had a positive influence on guest satisfaction (Y). The Adjusted R Square value was 0.334, which showed the contribution of the influence of the facility variable by 33.4%, and the remaining 66.6% was influenced by other variables that were not studied